The Fuzzy Logic Approach for Modelling Object Physical Features and Holes Occupancies - Syed Abdul Hamid , Syed Mohamad Shazali; Sulaiman , Marizan; Said, Mohamed Azmi (2008)
Abstract— This paper introduces the fuzzy logic approach for modelling object physical features and holes occupancies. There are four major algorithms involved. They are known as coloured balls detection, holes recognition, cupboard’s holes’ position modelling and pixel coordinate system (PCS) to robot coordinate system (RCS) conversion. The inputs are received from a webcam which is not calibrated. This project introduces how to assist a robot arm system using vision system for making decision during conducting an operation or task. The system discussed in this paper had successfully tested and no camera calibration needed because the system has self calibration effect since the cupboard had modelled by the information of the holes of the cupboard and not by it environment. This system is generated in on-event processes and suitable for indoor environment applications with low time frame rate camera. This project introduces how to assist a robot arm system using vision system for making decision during conducting an operation or task. One of the advantages of this project is that it only used a camera and image processing generated by the algorithms itself without additional sensor such as sonar or IR sensor.